Business Mathematics - Kaliski, Burton S. (New York : Harcourt Brace Jovanovich, 1982)
Provides the principles for solving business problems and creates awareness of the importance of business mathematics in personal life.
Includes index.
oif 11/02/15, ijb 20/03/2019
Loan
Keywords: Business mathematics